(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research dealt with the process of reducing costs through some strategic methods of management accounting targeted cost analysis unassembled and Alkeisen, where he focused this research through his theory on a review of some administrative accounting strategic technologies, while the second practical side through the application of targeted cost analysis unassembled and Alkeisen, acquired Search importance of focusing on the decisions to cut costs, through the use of some administrative accounting strategic methods and this we can unassembled analysis, continuous improvement, and the cost of quality) when applied quality, "in light of this has been reached to a set of conclusions that the most important of the company’s reliance on traditional methods of calculating the cost of products and hence the lack of a causal relationship between the bases used in distribution centers and cost caused in cost occurs, and the most important recommendations the need to adopt economic units on modern management techniques to improve Production processes because of its large andprominent role in promoting the competitiveness of these units in the face of the currentenvironment accelerated change and reflected from the achievement of the objectives of the unit in the survival, growth and continue to offer low prices and high quality products.